Myosin VI drives arrestin-independent internalization and signaling of GPCRs - Nishaben M. Patel; Léa Ripoll; Chloe J. Peach; Ning Ma; Emily E. Blythe; Nagarajan Vaidehi; Nigel W. Bunnett; Mark von Zastrow; Sivaraj Sivaramakrishnan (Nature Communications)
Abstract G protein-coupled receptor (GPCR) endocytosis is canonically associated with β-arrestins. Here, we delineate a β-arrestin-independent endocytic pathway driven by the cytoskeletal motor, myosin VI. Myosin VI engages GIPC, an adaptor protein that binds a PDZ sequence motif present at the C-terminus of several GPCRs. Using the D2 dopamine receptor (D2R) as a prototype, we find that myosin VI regulates receptor endocytosis, spatiotemporal localization, and signaling. We find that access to the D2R C-tail for myosin VI-driven internalization is controlled by an interaction between the C-tail and the third intracellular loop of the receptor. Agonist efficacy, co-factors, and GIPC expression modulate this interaction to tune agonist trafficking. Myosin VI is differentially regulated by distinct GPCR C-tails, suggesting a mechanism to shape spatiotemporal signaling profiles in different ligand and physiological contexts. Our biophysical and structural insights may advance orthogonal therapeutic strategies for targeting GPCRs through cytoskeletal motor proteins.